Evaluation of feral swine as potential reservoirs, sentinels, and vectors of emerging and re-emerging zoonotic pathogens in the United States - Maison, Rachel Marie, author; Bosco-Lauth, Angela, advisor; Bowen, Richard, advisor; Borlee, Bradley, committee member; Brown, Vienna, committee member; Han, Sushan, committee member (Colorado State University. Libraries, 2023)
Feral swine are an extremely adaptable and prolific invasive species present in many regions of the United States. A generalist diet, high reproductive capacity, and opportunistic nature make them a significant threat to native flora and fauna, and their destructive foraging behaviors have been attributed to substantial crop loss and property damage throughout their range. Feral swine have also been demonstrated as vectors and reservoirs for many diseases, some of which are transmissible to humans. Despite the efforts of government agencies to impede range expansion of feral swine and monitor populations for disease, human-mediated movements as well as continued natural dispersal in some regions have made management difficult. Subsequently, this invasive species continues to threaten human and animal health throughout its current range. Reported herein are a series of laboratory and field-based investigations that seek to address the potential role(s) of feral swine in the epidemiology of a few zoonotic pathogens that are emerging or re-emerging in the United States. As pigs interact closely with soils through their natural rooting and wallowing behaviors, we were primarily interested in soil-dwelling zoonoses, and identified three of particular interest. The two bacterial species Bacillus anthracis and Burkholderia pseudomallei, as well as the fungus Coccidioides, are the causative agents of anthrax, melioidosis, and coccidioidomycosis respectively, and each is understudied as they relate to feral swine. While each of these organisms is unique in their biology and the relative threat(s) they've posed to humans and animals throughout their respective histories, they are similar in that much of their ecology remains undescribed. The often-complex ecological relationships exhibited by pathogenic organisms are vital to their continued survival and evolution and can play an important role in their dissemination to human populations. The presence of high-density populations of feral swine in many regions of the United States, as well as their ability to occupy a range of habitats, may be playing a significant role in the persistence and dissemination of these organisms. Furthermore, the interactions of feral swine with contaminated substrates within their environment, as well as high levels of interspecies interactions throughout their current range could make them a likely source of additional emerging or novel pathogens. After a summary of the literature concerning feral swine in the United States, followed by that for the causative agents of anthrax, coccidioidomycosis, melioidosis, and a few select emerging disease threats, each respective chapter within this work details investigations largely by pathogen. Within Chapter 2, we present the results of a field serosurvey in feral swine residing across regions of known anthrax endemicity in Texas, and retrospectively document bacterial exposure via enzyme-linked immunosorbent assay (ELISA). This study was performed principally to evaluate the biosentinel utility of feral swine for anthrax contaminated environments, and the ELISA utilized was developed and optimized for detecting antibodies of swine origin to B. anthracis protective antigen. We additionally report on a laboratory-based experimental infection study where which a group of juvenile feral swine were either intranasally or subcutaneously exposed to varying amounts of B. anthracis strain Sterne 34F2 spores, and seroconversion as well as bacterial shedding through the nasal passages documented over time. Through both the field-based serosurvey, as well as the experimental inoculation study, we report that feral swine serology may be used as a management strategy to indirectly identify regions contaminated with anthrax bacteria. Moreover, we report that some feral swine intranasally exposed to high amounts of B. anthracis Sterne contained detectable and viable spores within their nasal passages up to 56 days past their initial exposure event as demonstrated by bacterial culture. The presence of viable B. anthracis within the nasal mucosa well after an exposure event suggests that feral swine may be capable of spreading infectious anthrax bacteria as mechanical vectors. Chapter 3 of this work details an experimental infection study similar to that reported in the previous chapter, however, instead intranasally exposes a group of juvenile feral swine to Coccidioides posadasii strain Silveira spores. This study was performed to evaluate the pathogenesis and immune response of feral swine to one of the causative agents of coccidioidomycosis. Fungal culture of tissues collected from inoculated individuals at necropsy was performed to assess whether animals might act as reservoirs for the fungus in addition to describing the characteristics of infection. Feral swine utilized for this study did not display overt clinical signs of disease, and despite being inoculated with a large dose of fungal spores, also did not seroconvert based on the results of porcine agar gel immunodiffusion assays. Fungal culture of lung and mediastinal lymph node tissues of a subset of pigs revealed the presence of viable C. posadasii, however, examination of additional sections of the same tissues did not reveal the presence of the granulomatous lesions often associated with coccidioidomycosis. Most individuals had significant comorbidities as illustrated via histology, most notably Metastrongylus nematodes in the lungs. Despite an absence of lesions and organisms histologically, isolation of the fungus from tissues by culture indicated active infection and imply that feral swine are mildly susceptible to acute Coccidioides infection. These results suggest that in some instances, feral swine may aid in fungal dispersal on the landscape due to the presence of spherules in tissues post-mortem. Chapter 4, concerning melioidosis, reports on laboratory-based experiments evaluating an indirect ELISA for measuring antibodies to B. pseudomallei in domestic and wild swine. Described previously to test human sera, this ELISA utilized whole-cell lysate derived from B. pseudomallei strain Bp82 and was optimized and preliminarily validated by testing sera from domestic goats and domestic swine experimentally inoculated with virulent and avirulent strains of B. pseudomallei, respectively. Further evaluation of assay specificity was performed by testing sera against similar antigen preparations of the closely related bacterial species Pseudomonas aeruginosa strain PAO1. Examination of sera from laboratory animals against Bp82 and PAO1 whole-cell lysate antigens revealed that most animals seroconverted and displayed B. pseudomallei antibodies, and that little cross-reactivity existed between antigens. After preliminary assay validation, serum from wild pig populations originating from Arizona, California, and Puerto Rico were assessed using both antigens to document B. pseudomallei exposure in wild pigs residing in regions where bacterial absence or endemicity can be confidently inferred at this time. In stark contrast to the serology displayed by laboratory animals, analysis of field sera collected from these regions demonstrated high levels of cross-reactivity between Bp82 and PAO1 antigens, suggesting the assay is not suitable for use in wild pig populations. Lastly, Chapter 5 describes a general survey of feral swine removed from the Aransas National Wildlife Refuge in Texas for each of the organisms investigated in the proceeding chapters, as well as additional bacterial and viral pathogens; added pathogens that were included within this survey included Francisella tularensis, and SARS-CoV-2, the causative agents of tularemia and COVID-19, respectively. A suite of samples, including external parasites (e.g., ticks), nasal swabs, blood, and a series of tissues were collected from each feral swine in the field and analyzed by bacterial and fungal culture, serology, and viral assays to determine if any pigs were actively infected or previously exposed to a range of pathogens. General and selective culture of tissue samples did not reveal active infection with B. anthracis, Coccidioides spp., B. pseudomallei, or other pathogenic bacteria, however, serology illustrated that a subset of pigs were previously exposed to B. anthracis. Further examination of tissues histologically illustrated a high degree of parasitic infection in the majority of pigs, particularly with Metastrongylus nematodes. Finally, three ixodid tick species, all adults, were collected off of the majority of feral swine sampled, none of which appeared to be carrying infectious virus based on the results of general cytopathic effects assays. Results generated for this study further confirm that feral swine are hosts for a range of ixodid ticks present in Texas and include species that are known to pose a risk to the health of livestock, wildlife, and humans. Moreover, serological results indicating previous exposure to anthrax-causing bacteria agree with past ecological modeling studies that have suggested environmental suitability for B. anthracis in the region of Aransas National Wildlife Refuge. Taken together, these investigations demonstrate that feral swine in the United States very likely are contributing to the ecology of anthrax and coccidioidomycosis by being mechanical vectors and possible reservoirs of B. anthracis and Coccidioides, respectively. Serological data demonstrated from field and laboratory studies additionally support the use of feral swine as biosentinels within landscapes undergoing invasive species management and that may be contaminated with B. anthracis. While the serological data generated through the B. pseudomallei investigations reported here currently do not support use of a crude whole-cell lysate-based ELISA to evaluate samples collected from the field, we hypothesize that feral swine may be reservoirs and/or vectors of melioidosis-causing bacteria. Future investigations should continue to examine additional antigens for serologic testing, as laboratory-infected swine demonstrated a measurable antibody response after intranasal exposure with Bp82. Additional follow-up studies should also be conducted to further describe the relative role(s) that feral swine may play in the ecology and epidemiology of B. anthracis and Coccidioides, particularly if regions with high incidence of animal or human disease correspond with high densities and activity of feral swine. Future research should continue to screen feral swine as well as the ectoparasites that feed upon them for emerging or re-emerging pathogens, especially in areas with high biodiversity or species of conservation concern, as well as in areas with high levels of human activity.
Keywords: coccidioidomycosis; feral swine; Sus scrofa; emerging diseases; anthrax; melioidosis